Therapeutic potential of CPI-613 for targeting tumorous mitochondrial energy metabolism and inhibiting autophagy in clear cell sarcoma - Egawa, Yuki; Saigo, Chiemi; Kito, Yusuke; Moriki, Toshiaki; Takeuchi, Tamotsu (PLOS ONE, 2018)
Clear cell sarcoma (CCS) is an aggressive type of soft tissue tumor that is associated with high rates of metastasis. In the present study, we found that CPI-613, which targets tumorous mitochondrial energy metabolism, induced autophagosome formation followed by lysosome fusion in HS-MM CCS cells in vitro. Interestingly, CPI-613 along with chloroquine, which inhibits the fusion of autophagosomes with lysosomes, significantly induced necrosis of HS-MM CCS cell growth in vitro. Subsequently, we established a murine orthotropic metastatic model of CCS and evaluated the putative suppressive effect of a combination of CPI-613 and chloroquine on CCS progression. Injection of HS-MM into the aponeuroses of the thigh, the most frequently affected site in CCS, resulted in massive metastasis in SCID-beige mice. By contrast, intraperitoneal administration of CPI-613 (25 mg/kg) and chloroquine (50 mg/kg), two days a week for two weeks, significantly decreased tumor growth at the injection site and abolished metastasis. The present results imply the inhibitory effects of a combination of CPI-613 and chloroquine on the progression of CCS.